Experimental and theoretical analysis of the recombination processes in GaInNs 1.3 μm lasers - Choulis, Stelios A.; Tomić, Stanko S.; Fehse, Robin (My University, 2002)
By measuring the spontaneous emission from normally operating ∼1.3 μm GaInNAs/GaAs-based lasers we have quantitatively determined the variation of each of the current paths present in the devices as a function of temperature from 130 K to 370 K
Keywords: Electrons; Nitrogen; Quantum wells; Resonance; Gallium arsenide; Indium compounds